PERAN GURU PENDIDIKAN KEWARGANEGARAAN DALAM MEMBANGUN KARAKTER KEPEMIMPINAN PESERTA DIDIK - Arsali Arsali; Aryanti Dwi Untari (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
This study aims to determine how the professionalsm of teachers in increasing the learning motivation of grade VII D student in MTs Al-Khairiyah Pipitan. the research method used is descriptive analysis research with a qualitative approach. Date collection techniques used by researchers in this study are through observation, interviews and documentation. The source of data in this qualitative research is the information directly from sources of information that are consideret to be related to the professionalism of PPKn teacher in MTs Al-Khairiyah Pipitan.The results of the study showed that the professionalsm of the teachers of PPKn at MTs Al-Khairiyah pipitan had specialized expertise by an expertise or specialization education program. have the ability to understand students. the ability to develop learning outcomes assessment tools and the learning process. Based on the results of research that PPKn teacher professionalsm offorts to improve student motivation by giving number/prizes, prizes,rivals/competitions,and giving tests.